Da'wah Message on the YouTube Channel Hobby Makan: (Stuart Hall Theory Reception Analysis) - Javier Ardyansyah, Alim; Suprabowo, Imam (Universitas Muhammadiyah Yogyakarta, 2022)
Dawah activities in the technological era are not only done conventionally but can also be done through various media. Currently, da'i or da'wah activists through the internet and social media. One of them is the Hobby Makan channel. This research aims to find out the message of da'wah and the meaning of da'wah messages carried out by the Hobby Makan YouTube channel. This research uses descriptive qualitative by using Stuart Hall's reception analysis approach through interviews, observations, and documentation of 6 informants consisting of students of the Universitas Muhammadiyah Yogyakarta, non-Muhammadiyah Islamic University, and public universities, both public and private. The results of this study can be concluded that this channel gives more of a message of da'wah in terms of charity, especially in sharing and giving. Stuart Hall’s 3 audience messages of reading positions consist of dominant position, negotiation position, and oppositional position, respectively.